High‐resolution mitochondrial DNA analysis sheds light on human diversity, cultural interactions, and population mobility in Northwestern Amazonia. Issue 2 (27th October 2017) - Arias, Leonardo; Barbieri, Chiara; Barreto, Guillermo; Stoneking, Mark; Pakendorf, Brigitte
Abstract: Objectives: Northwestern Amazonia (NWA) is a center of high linguistic and cultural diversity. Several language families and linguistic isolates occur in this region, as well as different subsistence patterns, with some groups being foragers and others agriculturalists. In addition, speakers of Eastern Tukanoan languages are known for practicing linguistic exogamy, a marriage system in which partners are taken from different language groups. In this study, we use high‐resolution mitochondrial DNA sequencing to investigate the impact of this linguistic and cultural diversity on the genetic relationships and population structure of NWA groups. Methods: We collected saliva samples from individuals representing 40 different NWA ethnolinguistic groups and sequenced 439 complete mitochondrial genomes to an average coverage of 1, 030×. Results: The mtDNA data revealed that NWA populations have high genetic diversity with extensive sharing of haplotypes among groups. Moreover, groups who practice linguistic exogamy have higher genetic diversity, while the foraging Nukak have lower genetic diversity. We also find that rivers play a more important role than either geography or language affiliation in structuring the genetic relationships of populations. Discussion: Contrary to the view of NWA as a pristine area inhabited by small human populations living in isolation, our data support a view of high diversity and contact among different ethnolinguistic groups, with movement along rivers probably facilitating this contact. Additionally, we provide evidence for the impact of cultural practices, such as linguistic exogamy, on patterns of genetic variation. Overall, this study provides new data and insights into a remote and little‐studied region of the world.